Convective thermal and concentration transfer effects in hydromagnetic peristaltic transport with Ohmic heating - F.M. Abbasi; S.A. Shehzad (Journal of Advanced Research, 2017)
The primary theme of this communication is to employ convective condition of mass transfer in the theory of peristalsis. The magnetohydrodynamic (MHD) peristaltic transport of viscous liquid in an asymmetric channel was considered for this purpose. Effects of Ohmic heating and Soret and Dufour are presented. The governing mathematical model was expressed in terms of closed form solution expressions. Attention has been focused to the analysis of temperature and concentration distributions. The graphical results are presented to visualize the impact of sundry quantities on temperature and concentration. It is visualized that the liquid temperature was enhanced with the enhancing values of Soret-Dufour parameters. The liquid temperature was reduced when the values of Biot number were larger. It is also examined that mass transfer Biot number for one wall has no impact on transfer rate. Different mass transfer Biot numbers generate a non-uniform concentration profile throughout the channel cross section.